2011
DOI: 10.1038/nrneph.2011.105
|View full text |Cite
|
Sign up to set email alerts
|

Spondylodiscitis in a patient on chronic hemodialysis

Abstract: Antibiotic therapy with intravenous cefazolin for 6 weeks and oral minocycline for 2 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
2
9
0
1
Order By: Relevance
“… 3–5 Urinary tract infection and intra-abdominal infection are also risk factors for infective spondylodiscitis from Gram-negative bacteria following contiguous spread of the pathogen. 5 , 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3–5 Urinary tract infection and intra-abdominal infection are also risk factors for infective spondylodiscitis from Gram-negative bacteria following contiguous spread of the pathogen. 5 , 6 …”
Section: Discussionmentioning
confidence: 99%
“…Patients in our study might have had insidious onset of back pain that took months from initial symptoms until diagnosis, in accordance with previous reports. 6 , 11 , 12 Only one study reported that fever was the most frequent initial presentation, but almost all patients in that study eventually developed back pain during hospitalization. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Known predisposing risk factors include previous spine surgery, a distant infectious focus, diabetes mellitus, advanced age, intravenous drug use, HIV infection, immunosuppression, oncologic history, renal failure, rheumatological diseases, and liver cirrhosis [11][12][13].…”
Section: Epidemiologymentioning
confidence: 99%
“…Both bacterial and fungal infections can occur. Reports are few 1 – 6. We highlight such a case in a patient with diabetes, which resulted in death and highlight the use of MRI in diagnosis.…”
Section: Introductionmentioning
confidence: 83%